Tax Morale and Tax Mentality in Slovenia - Čokelc, Stanko; Križman, Ana (Naše gospodarstvo/Our economy, 2014)
The economic and financial crisis, which resulted in budget deficits in several countries, was the most evident cause generating authorities’ and researchers’ interest in the decisive factors influencing the behavior of individuals and corporations in tax matters. The question arises why taxpayers are willing to accept the tax policy of the state, why some avoid paying their taxes and why others voluntarily fulfil their tax obligations despite the relatively low detection risk. Empirical research indicates that the volition to pay one’s taxes cannot be sufficiently explained exclusively by external fa- ctors, such as tax rates, fines, and other risks (e.g., probability of a tax audit), but rather points to a complex interplay of causes and their interactions. Several external factors (societal, systemic, and situational) and a number of purely subjective factors (the indi- vidual’s character, motivation, and inner conscience, often referred to as tax morale) have been proven to affect the settlement of one’s tax obligations. Tax morale is thought to be one of the key factors affecting the behavior and actions of individuals with respect to the tax system. In our research, we aimed to provide an overview of the pre- sent findings from the most recent literature and position them in the context of the Slo- venian tax system. We attempted to discern how respondents view the Slovenian tax system, investigating their perception of tax morale and researching the factors linked to tax morale and tax behavior in light of the most recent findings in this field.